Pengaruh Profitabilitas, Solvabilitas Dan Financial Distress Terhadap Audit Delay Dengan Pemoderasi Reputasi Auditor - Hedar Rusman; Eha Hasni Wahidhani (CV. ULIL ALBAB CORP, 2026)
This research aims to verify and provide empirical evidences about:the effect of Profitability, Solvability, and Financial Distress to Audit Delay and to determine whether the reputation capable public accounting firms in moderating effect of profitability, solvability, and financial distress to the audit delay. The population of this research are manufacturing companies that listed in Indonesia Stock Exchange (BEI) during the period 2018 until 2022. The number of samples taken by purposive sampling technique are 499 data from manufacturing companies. The analysis tools used is Moderating Regression Analysis (MRA). The result of this research concluded that the variable of profitability have negative effect to Audit Delay and variable solvability and financial distress have positive to audit delay. Auditor Reputation have negative impact on audit delay. Auditor Reputation as moderating variable unable to strengthen the effect profitability to audit delay and auditor reputation as moderating able to weaken the effect solvability to audit delay and auditor reputation as moderating also able to to weaken the effect financial distress to audit delay.